Toxic Properties Under The Effect of Desmetrine - Mukhtorov Fazliddin; Salimov Yunus (International Journal on Orange Technologies, 2021)
In the scientific article, the toxicodynamic and toxicokenitic properties of the drug desmetrine, which belongs to the group of modern pyrethroids produced in India, were determined on the basis of experiments